THE RESULTS OF EXPERIMENTAL RESEARCHES OF NOISE REDUCTION PROCESS IN THE WORKING ZONE IN THE MANUFACTURE OF FERRO-CONCRETE STRUCTURES - Aleksandr Ivanovich Evtushenko (Современная наука и инновации)
The results of experimental studies to assess the acoustic efficiency of acoustic obstacle are presented depending on its thickness and material, and also from distance between a source of noise and an obstacle.